1997
DOI: 10.1046/j.1365-201x.1997.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous swim training impairs mitochondrial function in post‐ischaemic rat heart

Abstract: The effect of rigorous swim training (6 h day-1, 5 days week-1 for an average of 191 h) on mitochondrial respiratory function was investigated in rat heart subjected to in vivo ischaemia reperfusion (I-R). Mitochondria was isolated from the risk region of the left ventricle subjected to 60 min occlusion of the main left coronary artery followed by 30 min reperfusion. Heart weight and heart-to-body weight ratio was increased by 21 and 28% (P < 0.01), respectively, in the trained (T, n = 15) vs. control rats (C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…As Mn SOD represents an important antioxidant protection in heart mitochondria, a severe (˜40%) down‐regulation of this enzyme might render the organelle less protective thereby affecting its bioenergetic capacity. Glutathione depletion caused by rigorous swim‐training has been shown to decrease Mn SOD along with impaired state 43 respiration in rats (Leichtweis et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As Mn SOD represents an important antioxidant protection in heart mitochondria, a severe (˜40%) down‐regulation of this enzyme might render the organelle less protective thereby affecting its bioenergetic capacity. Glutathione depletion caused by rigorous swim‐training has been shown to decrease Mn SOD along with impaired state 43 respiration in rats (Leichtweis et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…see [71]). However, much controversy has been noticed re- garding those effects on myocardial mitochondria, particularly with training-induced increased mitochondria volume/density indirectly measured by cardiac citrate synthase activity [45,53,56]. In contrast to skeletal muscle, in which adaptive changes in the volume fraction of mitochondria can readily occur, increases beyond 35% are not so frequent in cardiac muscle, possibly because this would encroach on the volumes of contractile myofibrils and sarcoplasmatic reticulum within the cardiomyocyte and hence, limit heart performance [29].…”
Section: Exercise and Cardiac Mitochondrial Respirationmentioning
confidence: 99%
“…Data from Leichtweis et al [45] revealed a significant decrease in state 4 respiration of heart mitochondria from rats submitted to a vigorous swim training program (6 h´day ±1 ; 5 days´week ±1 , 8± 9 weeks) using malate-pyruvate and 2-oxoglutarate as respiratory energizer substrates. This unexpected change induced by training occurred in heart mitochondria from both sham and ischemia-reperfused (I-R) rats.…”
Section: Exercise and Cardiac Mitochondrial Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leichtweis et al 23 Rats One of the most comprehensive studies investigating the role of exercise training in regulating endogenous cardiac antioxidant defenses was reported by Powers and colleagues. 17 In this work, rats were treadmill-trained for 10 weeks at three different durations of daily run time (30,60, and 90 min).…”
Section: Trainingmentioning
confidence: 99%